Non-take-up of Tax-favored Savings Plans: Are Household Portfolios Optimal? - Rob Alessie; Stefan Hochguertel; Arthur van Soest (Tinbergen Institute, 2001)
Since the early nineties, the Dutch tax system allows for a tax-favored form of risk free savings through employer-sponsored savings plans (ESSPs). Under some conditions and up to a certain amount, the contributions to this planare tax-deductible, and the returns as well as the withdrawals are tax-free. This makes these plans extremelyattractive, with real after-tax returns by far exceeding the returns to other financial assets such as risk free savingaccounts or stocks and bonds. It suggests that those who have access to this type of savings should participate inthem, provided they have some financial wealth that they can allocate to their own choice. Moreover, unless liquidfinancial wealth is too small, each household should hold the maximum amount to which the tax incentives apply.In this paper, we analyze household data on participation in ESSPs. For those who have access to the asset, weinvestigate the relationship between the ownership decision, the amount held, substitution of other savings, andbackground characteristics. We find that people who are likely to face binding liquidity constraints less often buyESSPs and, if they buy them, more often use them as a substitute for other savings. Regular smokers often do nothold ESSPs, suggesting that some people in this group do not compose their portfolios optimally. The resultsquestion the assumption of rational financial decision making, which is typically maintained in theoretical as well asempirical work on savings and portfolio choice.
Keywords: C33; C35; D12; D91; 330; saving behavior; portfolio choice; Sparen; Steuervergünstigung; Portfolio-Management; Theorie